If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4 + -3b) = -8(-1b + 4) (4 * -2 + -3b * -2) = -8(-1b + 4) (-8 + 6b) = -8(-1b + 4) Reorder the terms: -8 + 6b = -8(4 + -1b) -8 + 6b = (4 * -8 + -1b * -8) -8 + 6b = (-32 + 8b) Solving -8 + 6b = -32 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. -8 + 6b + -8b = -32 + 8b + -8b Combine like terms: 6b + -8b = -2b -8 + -2b = -32 + 8b + -8b Combine like terms: 8b + -8b = 0 -8 + -2b = -32 + 0 -8 + -2b = -32 Add '8' to each side of the equation. -8 + 8 + -2b = -32 + 8 Combine like terms: -8 + 8 = 0 0 + -2b = -32 + 8 -2b = -32 + 8 Combine like terms: -32 + 8 = -24 -2b = -24 Divide each side by '-2'. b = 12 Simplifying b = 12
| 3k^2+73=33k | | -1+3x=-13x | | 2y(4)= | | -8x+2= | | -10q+5y+6-2q-y-6= | | -3(b+7)=6(b+4) | | 0=3x^2-6x+5 | | =(n+2)(2n+5) | | 2-82x=122 | | 2x+ine^4x=12 | | 17x+5=19x-7 | | 2x+10=2x-20 | | y=12+6x | | 6(5a+7)-7(-6-6a)=-60 | | 15-3b=12-2b | | 82-122x=2 | | 9x-7w+4x+6y+2y+3w= | | 8x-9=10-9x+12-x | | 39-(x+9)=7x-2 | | 4x^2+12x+81=0 | | 2x^2+2x=15 | | 3a=15-2a | | y=-4+x | | 7y-5-y-3= | | 122-82x=2 | | -8(4+6p)+8(1-6p)=72 | | -8x-9=10-9x+12-x | | 6x-30=34-2x | | 5+49x=21x+37 | | -0.5=-0.25(c+7) | | 4x+7=56 | | 0=27+v-4(3+v) |